Analisis Dispersi Karbon Monoksida (CO) Dari Kegiatan Transportasi Di Jalan HR. Soebrantas Kota Pekanbaru - Alfarobi, Muhammad Hardi; Sasmita, Aryo; Hafidawati, Hafidawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
HR. Soebrantas street is classified as a secondary arterial road that used to accommodate high traffic capacity. Traffic activity at this street will affect the amount of CO emissions generated from the vehicles. The purpose of this study is to comparing the estimate data the distribution of carbon monoxide (CO) emissions emitted from vehicles crossing HR. Soebrantas with ambient air quality standard based on Government Rule No. 41/1999. The method used is measuring the wind speed, exhaust height, traffic counting the vehicles and estimated by Gaussian Line Source. The results of this study show that the CO concentrations from the Gaussian model on Wednesday has exceeded the quality standard. Keywords : Carbon Monoxide, Gaussian Line Source, HR. Soebrantas Street, Wind Speed